2003
DOI: 10.1046/j.1472-765x.2003.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenolic monomers on biomass and hydrolytic enzyme activities of an anaerobic fungus isolated from wild nil gai (Baselophus tragocamelus)

Abstract: Aims: To test the anaerobic fungus, Piromyces sp. FNG5, for its tolerance to phenolic monomers released in the rumen by degradation of lignocellulosic poor-quality feeds. Methods and Results: Effects of phenolic monomers on biomass and fibrolytic enzyme activities of a pure culture of lignocellulolytic anaerobic fungus (Piromyces sp. FNG5) isolated from faeces of wild nil gai (blue bull, Baselophus tragocamelus) were evaluated. There was a reduction in fungal biomass at 1 mM M concentration of catechol with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Carboxymethylcellulase (CMCase) and xylanase activities were estimated as described earlier [14][15][16]. The reaction mixture used for the estimation of these enzymes contained: 1.0 mL phosphate buffer (pH 6.8, 0.1 M), 0.5 mL substrate (1% carboxymethylcellulose and 0.25% xylan from oat spelt) and 0.5 mL enzyme; incubated at 39 °C for 1 h for CMCase and 30 min for xylanase.…”
Section: Estimation Of Enzymesmentioning
confidence: 99%
“…Carboxymethylcellulase (CMCase) and xylanase activities were estimated as described earlier [14][15][16]. The reaction mixture used for the estimation of these enzymes contained: 1.0 mL phosphate buffer (pH 6.8, 0.1 M), 0.5 mL substrate (1% carboxymethylcellulose and 0.25% xylan from oat spelt) and 0.5 mL enzyme; incubated at 39 °C for 1 h for CMCase and 30 min for xylanase.…”
Section: Estimation Of Enzymesmentioning
confidence: 99%
“…Nelson et al (1995) tested ferulic acid, pyrogallol, gallic acid, and p-coumaric acid upto 40 mM concentration in the medium and found most of the isolates were able to tolerate gallic and vannilic acid but they were not able to tolerate ferulic acid and pyrogallol at the highest concentration. The fungal isolates from neelgai also showed variability in the tolerance to phenolic monomers (Paul et al 2004). …”
Section: Resultsmentioning
confidence: 99%
“…In one of our earlier studies it has been observed that an anaerobic fungus (Piromyces sp FNG5) isolated from the faeces of the wild blue bull (Boselophus tragocamelus) has high lignocellulolytic enzyme-producing ability and degrades phenolic monomers extensively. 10 Addition of culture of this fungal isolate significantly increased the lignocellulolytic ability of mixed rumen microflora of buffalo under both in vitro and in vivo conditions. 11 As the tannins are also phenolic compounds and as the fungal isolate was obtained from a wild herbivorous animal (blue bull) which survives on poor-quality tannin-rich hard stem herbages, our hypothesis was that the fungal isolate might have the ability to degrade or tolerate tannins and that introduction of such fungus into the rumen of domestic buffaloes (which had had no prior exposure to tannins) would enhance digestion of tannin containing feed.…”
Section: Introductionmentioning
confidence: 89%
“…The fungal isolate had very high lignocellulolytic enzyme-producing ability and degraded phenolic monomers extensively. 10,11 The fungal isolate exhibited the highest carboxymethyl cellulase, xylanase, β-glucosidase, feruloyl esterase, p-coumaroyl esterase, protease and acetyl esterase activity among 32 isolates from Indian domestic (buffalo, goat and sheep) and wild (hog deer, spotted deer, black buck and blue bull) ruminants. The fungal strain was maintained by weekly transfer of 5% culture to fresh liquid medium containing 0.02% cellobiose and 0.5% wheat straw as carbon sources.…”
Section: Materials and Methods Fungal Strain And Preparation Of Fungamentioning
confidence: 99%
See 1 more Smart Citation